Cephalometric evaluation of nanda type facemask in class III patients - Khalaf, Alaeddin Abu (My University, 2000)
1 Özet Bu araştırma, Nanda tarafından 1980´da tanıtılan modifiye yüz maskesinin incelenmesi için yapılmıştır. Marmara Üniversitesi Diş Hekimliği Fakültesi Ortodonti Anabilim dalına tedavi amacıyla gelen hastalardan 13 hasta alınmıştır (8 kız, 5 erkek). Yaşları 11.25 ile 15.16 arasında değişmektedir ve yaş ortalaması 13.66'dır. Diş yüzeylerinin akrilikle kaplandığı ve Hyrax vidasının kullandığı üst çeneyi genişletme apareyi yapılmıştır. 7 gün maxillanın genişletilmesi yapılmıştır. Yedinci günde maxillanın ileri alma işlemi başlatılmıştır. İleri alma işlemi Petit tip yüz maskesi ve özel bükülmüş yüz arkı ile yapılmaktadır. Premolar dişlerin kökleri arasında olan maxillanın direnç merkezinden kuvvet uygulayabilmek için yüz arkı 2 cm yukarı bükülmüştür. Ortalama tedavi süresi 7.3 aydır, ve overjet 3-4 mm olunca aparey çıkarılmıştır. Apareyin etkilerinin araştırılması için tedavidenönce ve apareyin çıkarıldığı gün olmak üzere 2 tane sefalometrik film alınmıştır. Alınan sonuçlar aşağıdaki gibidir: 1. Maxilla A noktası 2.1 mm olacak şekilde öne gelmiştir. 2. SN-palatal düzlem açısının artmasıyla belirlenen, maxıllanın ön kısmının aşağı doğru rotasyonyaptığı gözlenmiştir. 3. Üst keserler dikleşmiştir. 4. Yumuşak doku profili düzelmistir. 5. Alt çene aşagı ve geri rotasyon yapmıştır. Sonuç olarak, kuvvetin uygulama noktası daha iyi kontrol edildeğinden bu aparey maxillanın ileri alınmasında etkili olmuştur. 2.

This research was performed to study the effects of the modified face bow introduced by Dr. Nanda in 1980. Thirteen patients ( 8 girls, 5 boys) were taken for the treatment from the patient coming to the orthodontic department, Marmara University. Their ages ranged from 11.25 yrs to 15.16 yrs with mean age of 13.66 yrs. Hyrax expansion screw with a full coverage acrylic cap splint was constructed, and rapid maxillary expansion was performed for 7 days. At the seventh day, protraction therapy was started . İt was composed of a specially bent face bow and a Petit type facemask. The face bow was bent upward 2 cm to provide point of force application at the center of resistance of maxilla, which is located between the apices of the premolars roots. The average treatment time was 7.2 months, and the appliance was removed when 3-4 mm of overjet was reached. Two Cephalograms were taken to study the effects of the appliance, one was before the treatment, and the other was at the same day of the appliance removal. The results were the following: 1. The maxilla moved forward indicated by point A 2.1 mm forward. 2. Anterior downward ( clockwise) rotation of the maxilla was achieved indicated by increase in the palatal plane angle in relation to S-N. 3. The maxillary incisors were uprighted. 4. Soft tissue profile was improved. 5. The mandible was rotated downward backward temporarly as an immediate effect afte splint removal As a conclusion the appliance was effective in bringing the maxilla forward as it allows better control of the point of force application, therefore, it prevents the unwanted anterior upward rotation of the maxilla that results from the conventional protraction therapy.
Keywords: Diş hekimliği; ORTODONTİ